Kaolin based protective barrier in municipal landfills against adverse chemo-mechanical loadings - Partha Das (Nature Portfolio, 2021)
Abstract In this work, we assess the self-sealing and swelling ability of the compacted granular bentonite (GB) under an inorganic salt environment and induced overburden stresses from the landfill waste. The laboratory permeation tests with high ionic strength salt solutions reveal that the GB fails to seal and exhibits a significant mechanical collapse under different applied stresses. The applicability of GB in the form of geosynthetic clay liners as the bottom liner facilities in landfills that produce high ionic strength salt leachates, therefore, remains a serious concern. We propose an additional barrier system based on kaolin, for the first time, to address this problem. The proposed kaolin-GB layered system performs satisfactorily in terms of its sealing and swelling ability even in adverse saline conditions and low overburden stresses. The kaolin improves the osmotic efficiency of the self and also helps the underlying GB layer to seal the inter-granular voids. The estimated design parameters by through-diffusion test suggest that the kaolin-GB layered system effectively attenuates the permeant flux and suitable as a landfill liner.